INDUSTRI 4.0: PENGARUH REVOLUSI INDUSTRI PADA KEWIRAUSAHAAN DEMI KEMANDIRIAN EKONOMI - Hamdan, Hamdan (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
The Industrial Revolution 4.0 is a new technological advancement that integrates the physical, digital and biological world, where there is a fundamental change in the human’s way of life. With the rapid development of technology that has experienced breakthroughs in all disciplines, including in the field of artifical intelligence, nanotechnology, biotechnology, internet-based technology has an impact on human life that can increase the economic growth too. The impact of economic growth has increased in the 4.0 industrial revolution where this can be seen from many business people and entrepreneurs who utilize the information technology, so that the basic principles of industrial design 4.0 are known as the digital revolution because of the proliferation of computers and automation and connectivity in a field. With the Industrial Revolution 4.0, there is an increasing influence in the economic sector, where the sector opens opportunities for entrepreneurship and MSMEs increase rapidly, thus giving an impact on entrepreneurship for economic independence.